The convergence of social media and other communication technologies in the promotion of illicit and controlled drugs. (24th December 2020) - Al-Rawi, Ahmed
Abstract: Some social media platforms have strict regulations regarding the promotion of illicit and controlled drug on their sites. This study attempts to examine whether social media outlets like Twitter, Flickr and Tumblr have implemented practical measures to stop the active promotion of such drugs. We examined over 2.6 million social media posts taken from these three platforms. By focusing on keyword searches around mobile apps and communication means, we found evidence of ongoing opioid drug promotion, especially on Twitter followed by Flickr and Tumblr; we discuss our approach which effectively identifies posts related to the promotion of opioids and controlled drugs.